2002
DOI: 10.1074/jbc.m107749200
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfection of H25A Mutant Heme Oxygenase-1 Protects Cells against Hydroperoxide-induced Cytotoxicity

Abstract: Heme oxygenase (HO)-1 is a stress-inducible enzyme protecting cells against oxidative stress, and mechanisms have been considered to depend exclusively on its enzyme activity. This study aimed to examine if the protein lacking catalytic activities could also display such resistance against oxidative stress. Stable transfectants of rat wild type HO-1 cDNA (HO-1-U937) and those of its H25A mutant gene (mHO-1-U937) were established using human monoblastic lymphoma cell U937. HO-1-U937 and mHO-1-U937 used in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 26 publications
2
79
0
Order By: Relevance
“…The data support our previous study, in which we showed that HO1 protects against NMDA-induced acute brain damage in mice (Ahmad et al, 2006). In addition, HO proteins likely have intrinsic cytoprotective properties (Hori et al, 2002;Kim and Doré, 2005). HO1 catalyzes the cleavage of heme (a pro-oxidant) to form iron (which can then increase ferritin levels), carbon monoxide (a vasodilator and anti-apoptotic agent), and biliverdin, which is rapidly reduced to bilirubin (an antioxidant) (Doré, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…The data support our previous study, in which we showed that HO1 protects against NMDA-induced acute brain damage in mice (Ahmad et al, 2006). In addition, HO proteins likely have intrinsic cytoprotective properties (Hori et al, 2002;Kim and Doré, 2005). HO1 catalyzes the cleavage of heme (a pro-oxidant) to form iron (which can then increase ferritin levels), carbon monoxide (a vasodilator and anti-apoptotic agent), and biliverdin, which is rapidly reduced to bilirubin (an antioxidant) (Doré, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, within a narrow therapeutic range, these catalytic by-products exert powerful antioxidant [15,31], antiinflammatory [32] and anti-apoptotic effects [33][34][35], leading to reduced infarct size [16,17,[36][37]. However, emerging evidence, suggests that HO-1 may also exert cytoprotective effects, independent of heme breakdown [38] by interacting with survival signaling pathways such as PI3K-Akt and p38. We reported recently that HO-1 functions co-dependently with Akt to confer protection from pro-oxidant-induced injury in human aortic smooth muscle cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Hori et al (39) transfected U937 macrophage-like cells with catalytically inactive HO-1, finding that these cells were still able to withstand peroxide challenge. Doré's laboratory demonstrated a protective effect of HO-2 during heme challenge both in vitro (40) and in vivo (41).…”
Section: Discussionmentioning
confidence: 99%